Mesenteric lymphangioma in childhood: a case report and narrative literature review - Jin Li; Le Luo; Yong Liu; Wenlan Li; Xin Wei (Frontiers in Oncology)
Lymphangioma is an uncommon benign neoplasm of the lymphatic system, predominantly observed in children and infants and infrequently in adults. Mesenteric lymphangioma is very rare. This article reports on the case of a 4-year-old female who was admitted to the hospital due to abdominal pain. Ultrasonography identified a cystic mass in the abdominal cavity, diagnosed as mesenteric lymphangioma, for which surgical intervention was advised. The patient underwent laparoscopic lesion resection with small bowel resection and anastomosis under general anesthesia. Pathological examination confirmed the diagnosis of mesenteric lymphangioma. In children, it frequently presents as an acute abdomen. Our comprehensive literature analysis strongly suggests that treatment decisions for pediatric mesenteric lymphangioma need to be guided by a careful assessment of individual patient presentations. Although exploratory laparotomy with tumor resection and involved bowel segment removal remains the gold-standard treatment, the advent of laparoscopic techniques and sclerotherapy has facilitated the evolution of personalized therapeutic strategies, potentially reducing dependence on conventional surgical approaches in the future.